Evaluation of an enzyme immunoassay for clinical diagnosis of neurocysticercosis in symptomatic patients - Carvalho Junior,Reynaldo Mendes de (2010)
INTRODUCTION: Neurocysticercosis is an infection of the human central nervous system caused by the metacestode larvae of Taenia solium. Neurocysticercosis is the most common parasitic disease in developing countries. Epilepsy is the most common clinical manifestation. Difficulties in confirming the diagnosis motivated the evaluation of the enzyme-linked immunosorbent assay on cerebral spinal fluid (CSF). METHODS: Twenty-two patients with NCC and 44 control patients were studied. CSF was analyzed using a commercial ELISA kit developed for NCC. Sensitivity and specificity were measured and a multivariate logistic regression was performed. RESULTS: Sensitivity and specificity of ELISA were 31.8% and 100%, respectively, with accuracy of 77.3%. Only the size of the lesions proved to be important for performance of the test. CONCLUSIONS: The results showed that ELISA contributes to the diagnosis of neurocysticercosis if the result is negative or if the patient has a lesion of 2 cm or more.